POLITICAL STABILITY, INDEX PERCEPTION OF CORRUPTION AND DIRECT FOREIGN INVESTMENT IN SOUTHEAST ASIA - Nairobi, Nairobi; Amelia, Nur (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.02.TAHUN.2022DO - 10.24843/EEB.2022.v11.i02.p06, 2022)
The incoming foreign direct investment will bring technology, new innovations, increase in capital, create jobs that will absorb unemployment, and improve the quality of human resources so that investment is considered important in accelerating economic growth in developing countries. The purpose of this study was to determine the effect of political stability and the Corruption Perception Index on Foreign Direct Investment in Southeast Asia. This study uses secondary data obtained from the World Bank, and Transparency International. The method used is a panel data model with a total cross-section of 10 (ten) countries in Southeast Asia and a time-series in 2010-2019. The research was conducted in 10 countries due to Timor-Leste because the country officially became a member of Southeast Asia in 2011. The research method used in this study is the Random Effect Model. The results showed that the independent variables of political stability, corruption perception index (GPA), and economic growth (EG) each had a significant and positive effect on foreign direct investment in Southeast Asia, while inflation and exchange rates had no effect on foreign direct investment. in Southeast Asia 2010-2019 period, ceteris paribus.